Business Education and the Mirage of Career Opportunities in Public and Private Sectors - Salau, K. K. (International Journal of Educational Management, 2022)
This paper focuses on the current trend in business education and the mirage of career opportunities. The paper discussed the concept of business education, the goals of business education, the concept of career opportunities, business education and career opportunities in the public and private sectors and problems facing business education. Conclusion was drawn and recommendations made among others are that, government should stop paying lip service to the development of business education, a vocational guidance programme should be introduced at the secondary school level to enable students make a realistic choice of career.